2021
DOI: 10.1371/journal.pone.0258964
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of lifetime survival and predictors of mortality among TB with HIV co-infected children after test and treat strategies launched in Northwest, Ethiopia, 2021; a multicentre historical follow-up study

Abstract: Introduction In resource-limited settings, the mortality rate among tuberculosis and human Immunodeficiency virus co-infected children is higher. However, there is no adequate evidence in Ethiopia in general and in the study area in particular. Hence, this study aims to estimate lifetime survival and predictors of mortality among TB with HIV co-infected children after test and treat strategies launched in Northwest Ethiopia Hospitals, 2021. Methods Institution-based historical follow-up study was conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…A total of seven studies [21,24,25,33,38,43,47] provided data on mortality rates among children and adolescents with HIV-TB co-infection across various age groups. The pooled mortality rates were 32% (95% CI [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] for those aged <12 months, 14% (95% CI [10][11][12][13][14][15][16][17][18][19] for the 1-5 years age group, 15% (95% CI 12-17) for the 5-10 years age group, and 16% (95% CI [13][14][15][16][17][18][19][20] for those aged over 10 years old (Figure 4, Supplemental Digital Content, http://links.lww.com/QAD/D142). As illustrated in Fig.…”
Section: Subgroup Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of seven studies [21,24,25,33,38,43,47] provided data on mortality rates among children and adolescents with HIV-TB co-infection across various age groups. The pooled mortality rates were 32% (95% CI [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] for those aged <12 months, 14% (95% CI [10][11][12][13][14][15][16][17][18][19] for the 1-5 years age group, 15% (95% CI 12-17) for the 5-10 years age group, and 16% (95% CI [13][14][15][16][17][18][19][20] for those aged over 10 years old (Figure 4, Supplemental Digital Content, http://links.lww.com/QAD/D142). As illustrated in Fig.…”
Section: Subgroup Analysesmentioning
confidence: 99%
“…3, a statistically significant lower risk of death was observed in the 1-5 years age group (OR 0.40; 95% CI 0.20-0.78; P < 0.05), the 5-10 years age group (OR 0.34; 95% CI 0.16-0.72; P < 0.05), and the over 10 years age group (OR 0.35; 95% CI 0.22-0.55; P < 0.05) when compared with those under 12 months. Data from nine studies [21,24,25,27,33,36,38,43,52] reported mortality rates among children and adolescents with HIV-TB co-infection, stratified by gender. The combined mortality rates were 12% (95% CI 9-16) for males and 10% (95% CI 7-16) for females (Figure 5, Supplemental Digital Content, http://links.lww.com/ QAD/D142).…”
Section: Subgroup Analysesmentioning
confidence: 99%
“…were HIV positive and in 2014, 12% of the 9.6 million new TB cases occurred in individuals with HIV. 3,4 According to the WHO 2019 report, TB caused 10.1 million new cases and 1.7 million deaths, making it the leading cause of death from a single infectious agent (9). In Africa, the resurgence of TB is linked to TB-HIV/AIDS connection and a shortage of skilled healthcare personnel, not control program deterioration 5,6 In Africa, TB is the second largest disease burden (25%), following Southeast Asia (44%) (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…The decline in the immune system exacerbates the reactivation of latent tuberculosis bacilli in the lungs. In 2012, out of 8.6 million tuberculosis cases, 13% were HIV positive and in 2014, 12% of the 9.6 million new TB cases occurred in individuals with HIV 3,4 . According to the WHO 2019 report, TB caused 10.1 million new cases and 1.7 million deaths, making it the leading cause of death from a single infectious agent (9).…”
Section: Introductionmentioning
confidence: 99%
“…1 TB-HIV coinfection also has a high case fatality rate and a lifetime risk. 8,9 HIV is one of the important factors contributing to the global increase in TB. Due to primary infection, re-infection increases the risk of progression from one stage of TB to the next.…”
Section: Introductionmentioning
confidence: 99%